Effects of different heat treatments on the antioxidant activity and ascorbic acid content of bitter melon, Momordica charantia - Ng, Zhi Xiang; Kuppusamy, Umah Rani (Instituto de Tecnologia de Alimentos - ITAL, 2019)
This study investigated the effects of different heat treatments, namely boiling, microwaving and pressure cooking, on the reduced ascorbic acid content and antioxidant activity in Momordica charantia extracts. The total antioxidant activity of M. charantia extracts was determined by ferric reducing-antioxidant power and 2,2-diphenyl-1-picrylhydrazyl radical scavenging assays. The reduced ascorbic acid content was estimated by ferric reducing-antioxidant power-ascorbic acid assay and confirmed by high performance liquid chromatography. Regardless of the cooking method, all cooked M. charantia extracts had significantly (p < 0.05) higher total antioxidant activity, radical scavenging potency and reduced ascorbic acid content than the uncooked sample. The decreasing order of reduced ascorbic acid in M. charantia was as follows: microwaved > boiled > pressure-cooked > uncooked. The reduced ascorbic acid in M. charantia strongly correlated with the total antioxidant activity (r = 0.958, p < 0.05) and radical scavenging potency (r= 0.951, p < 0.05). The principle component analysis showed that 87% of the variation in the antioxidant values of M. charantia extracts was attributed to the different cooking methods. Heat treatment either by boiling or microwaving for a short period of time (10 minutes) improved the reduced ascorbic acid content in the M. charantia extract. This study showed that the reduced ascorbic acid could be retained under high temperature and pressure in M. charantia extracts. © 2019 Instituto de Tecnologia de Alimentos - ITAL. All rights reserved.